Mega-beasts - Sabuda, Robert; Reinhart, Matthew (Cambridge, MA : Candlewick Press, 2007)
Using pop-up illustrations and fold out pages introduces some of the largest, and smallest, prehistoric animals.
Includes pop-ups and fold-out pages.
Keywords: Animals, Fossil -- Juvenile literature; Extinct animals -- Juvenile literature; Predatory animals -- Juvenile literature; Toy and movable books -- Specimens; Prehistoric animals; Extinct animals; Predatory animals; Toy and movable books